Sea surface temperature variability: Patterns and mechanisms - Deser, Clara (author); Alexander, Michael (author); Xie, Shang-Ping (author); Phillips, Adam (author) (Annual Review of Marine Science, 2010)
Patterns of sea surface temperature (SST) variability on interannual and longer timescales result from a combination of atmospheric and oceanic processes. These SST anomaly patterns may be due to intrinsic modes of atmospheric circulation variability that imprint themselves upon the SST field mainly via surface energy fluxes. Examples include SST fluctuations in the Southern Ocean associated with the Southern Annular Mode, a tripolar pattern of SST anomalies in the North Atlantic associated with the North Atlantic Oscillation, and a pan-Pacific mode known as the Pacific Decadal Oscillation (with additional contributions from oceanic processes). They may also result from coupled ocean-atmosphere interactions, such as the El Niño-Southern Oscillation phenomenon in the tropical Indo-Pacific, the tropical Atlantic Niño, and the cross-equatorial meridional modes in the tropical Pacific and Atlantic. Finally, patterns of SST variability may arise from intrinsic oceanic modes, notably the Atlantic Multidecadal Oscillation.